2021
DOI: 10.1038/s41386-020-00945-9
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective randomized pharmacogenetic study of topiramate for treating alcohol use disorder

Abstract: In a prior study, topiramate reduced heavy drinking among individuals who sought to reduce their drinking, with the effect moderated by a single nucleotide polymorphism (SNP; rs2832407) in GRIK1, which encodes the kainate GluK1 receptor subunit (Kranzler et al. 2014). The present study sought to replicate prospectively the effect of topiramate and rs2832407 in patients with DSM-5 alcohol use disorder (AUD) who sought to reduce or stop their drinking. We stratified the randomization on genotype (rs2832407*C-all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 28 publications
4
34
0
Order By: Relevance
“… For the study by medication effect. Study 1, Kranzler et al, (2014); Study 2, Kranzler et al (2021a); EA = European American; SIP = Short Index of Problems; SF‐12 = Short Form Health Survey; lnGGT = natural log of the gamma‐glutamyl transferase concentration. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… For the study by medication effect. Study 1, Kranzler et al, (2014); Study 2, Kranzler et al (2021a); EA = European American; SIP = Short Index of Problems; SF‐12 = Short Form Health Survey; lnGGT = natural log of the gamma‐glutamyl transferase concentration. …”
Section: Resultsmentioning
confidence: 99%
“…Full descriptions of the procedures for both studies can be found in the primary publications (Study 1, n = 138, Kranzler et al, 2014; Study 2, n = 170, Kranzler et al 2021a). In brief, 308 heavy drinking individuals were recruited to participate in 1 of 2 randomized, double‐blind, 12‐week trials in which they received up to 200 mg/day of topiramate or placebo.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CONSORT diagrams and a full description of the procedures for both studies are provided in the primary publications. 3,7…”
Section: Patients and Proceduresmentioning
confidence: 99%
“…Studies have found that those who quit smoking had higher rates of alcohol abstinence than those who had not quit smoking (Campbell et al, 1995;Friend & Pagano, 2005;Sobell & Sobell, 1996), which suggests that concurrent treatment of both TUD and AUD would be beneficial. One candidate medication is the anticonvulsant topiramate, a sulfamate-substituted fructopyranose derivative with both GABAergic and glutamatergic properties, which has been found to reduce drinking among those with AUD (Johnson et al, 2007;Kranzler et al, 2014Kranzler et al, , 2021. In a post hoc analysis extending their previously published report on topiramate's effects on reducing alcohol drinking (Johnson et al, 2003a), Johnson et al (2005) found that participants given topiramate were more likely to abstain from smoking than those given placebo.…”
Section: Introductionmentioning
confidence: 99%